Prosthodontists in Private Practice: Current and Future Conditions of Practice in the United States (Part I) - Kent D. Nash, PhD1 and David L. Pfeifer, DDS, MS, MEd2 (Journal of Prosthodontics, 2007)
The purpose of this study was to use data from surveys of prosthodontists to examine the current conditions and characteristics of prosthodontists in private practice in the United States.